Ethnic Identity, Thwarted Belongingness, and Perceived Burdensomeness Among Latinx and Black Adolescents in the United States - Carolina Vélez‐Grau; Melissa McTernan; Michael A. Lindsey; Laura Mufson (Psychiatric Research and Clinical Practice)
Objective Ethnic identity formation is one of the most important tasks of adolescence. There is limited information about ethnic identity and interpersonal factors associated with suicide ideation and their impact on mental health and wellbeing among Latinx and Black adolescents. This study examines ethnic identity, thwarted belongingness (TB), and perceived burdensomeness (PB) among Latinx and Black adolescents. Methods Latinx and Black adolescents were recruited from community agencies and completed self‐reports about interpersonal factors, ethnic identity, and demographics. Linear multiple regression models were used to evaluate the association between ethnic identity (MEIM composite score), TB, and PB, controlling for gender, age, ethnicity, income, country of birth, and language. Results Stronger ethnic identity was associated with lower TB but not PB. TB continued to be significant after adjusting the model. In this adjusted model, higher‐income was associated with higher TB and PB. In addition, speaking Spanish was associated with lower PB among Latinx youth. Conclusions The association between ethnic identity and TB suggests an opportunity for suicide prevention. Strengthening ethnic identity may reduce TB among Latinx and Black adolescents and, in turn, may lower suicide ideation. Ethnic identity interventions are universally available in schools, which makes the potential to use them readily accessible for adolescents, especially those with limited access to specialized mental health interventions and services.